Effect of Crocin and Voluntary Exercise on P53 Protein in Pancreas of Type2 Diabetic Rats - Vajihe Ghorbanzadeh, Mustafa Mohammadi, Gisou Mohaddes, Hassan Darishnejad, Leila Chodari (Tabriz University of Medical Sciences, 2017)
Background: Excessive apoptosis of the pancreatic beta-cell has been associated with type 2 diabetes. Hyperglycemia significantly stimulates pancreatic islet cell apoptosis. We evaluated the role of crocin and voluntary exercise on apoptosis of pancreas tissue in type2 diabetic rats. Methods: Animals divided into 5 groups as: control (Con), diabetes (Dia), diabetic-crocin (Dia-Cro), diabetic-voluntary exercise (Dia-Exe), diabetic-crocin-voluntary exercise (Dia-Cro-Exe). Type 2 diabetes was induced by high-fat diet (4 weeks) and injection of streptozotocin (STZ) (i.p, 35 mg/kg). Animals received crocin orally (50 mg/kg), voluntary exercise performed alone or together for 8 weeks. At the final of study, blood glucose levels and HbA1c were detected. Also p53 protein levels of pancreas tissue were measured by ELISA. Results: P53 levels in pancreas tissue of diabetic group were significantly higher than control group. Crocin and exercise significantly decreased the blood glucose, HbA1c levels and p53 expression in treated diabetic groups compared to diabetic group. The glucose, HbA1c and p53 levels were also significantly lower in crocin-voluntary exercise group in comparison to the other experimental groups. Conclusion: Our results reveal that both crocin and voluntary exercise reduce apoptosis of pancreas through reduction of p53 levels. Moreover, treatments with crocin and voluntary exercise have synergistic anti-apoptotic effects on pancreas tissue of type 2 diabetic rats. Protective effects of these interventions probably perform through the decreasing of glucose and HbA1c levels in blood of rats suffering from diabetes.